KEANEKARAGAMAN TUMBUHAN ANGIOSPERMAE DI ALUN-ALUN TUGU KOTA MALANG - Ahada Dewi Ayu Yulianti; Elfina Hari Murty; Lini Raudlotul Hikmiyah; Qurrota A'yuningtiyas; Salma Aulia Dwi Agustin; Syaifitri Rahmadhani; Indra Fardhani (Postgraduate, University of Mataram, 2023)
This research was conducted in Malang City Monument Square, East Java. The purpose of this study was to determine the diversity of angiosperm plants in Malang City Monument Square. This research was conducted using a quantitative method because it requires observation to obtain the desired data such as the types and characteristics of the angiosperm plants. In this study, sampling and identification of the morphology of the angiosperms were carried out by means of a descriptive analysis of the roots, stems and leaves. The analysis was carried out based on literature studies from various sources. Based on the results of these observations, 19 species of plants were found in Malang City Monument Square including Seroja, Nusa Indah Flowers, and Ganyong